Integration of Geochemical and Electrical Studies for Groundwater Quality in Parts of Hyderabad, A.P., India - G. Ramadass, G. Udaya Laxmi* and (Journal of Experimental Sciences, 2010)
Abstract In this paper an attempt is made to integrate the results of geo-electrical and geochemical studies and introduces the concept of IGQI which minimize the noise and enhance the signals over arising geochemical background. Integration of these methods are tested over the study areas (i) OU and surrounding area (ii) Katedan area will be combined with a view to critically analyzing the integration thus effected to traced the contaminated zones. Based on the IGQI, some prominent zones are coincided with the contaminated zones i.e. Ramanthapuram, North of Musi river, Uppal, Peddacheruvu, Nacharam, Mallapur, RKPuram cheruvu and Nadimi cheruvu in study area I and Katedan IDA, APAU and Sivarampally in study area II. Â  <div style="border-bottom: windowtext 1pt solid; border-left: medium none; padding-bottom: 1pt; padding-left: 0in; padding-right: 0in; border-top: medium none; border-right: medium none; padding-top: 0in; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Keywords: Integrated geochemical quality indicator (IGQI), Vertical Electrical Soundings(VES), Qualitative analysis Please Cite This Article As: Â  G. Udaya Laxmi and G. Ramadass. 2010. Integration of Geochemical and Electrical Studies for Groundwater Quality in Parts of Hyderabad, A.P., India. J. Exp. Sci. 1(6):32-35.